The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

Worldwide diversity in mammalian life histories: Environmental realms and evolutionary adaptations - E. Beccari; P. Capdevila; R. Salguero‐Gómez; C. P. Carmona (Ecology Letters, 2024)
Mammalian life history strategies can be characterised by a few axes of variation, conforming a space where species are positioned based on the life history strategies favoured in the environment they exploit. Yet, we still lack global descriptions of the diversity of realised mammalian life history and how this diversity is shaped by the environment. We used six life history traits to build a life history space covering worldwide mammalian adaptation, and we explored how environmental realms (land, air, water) influence mammalian life history strategies. We demonstrate that realms are tightly linked to distinct life history strategies. Aquatic and aerial species predominantly adhere to slower life history strategies, while terrestrial species exhibit faster life histories. Highly encephalised terrestrial species are a notable exception to these patterns. Furthermore, we show that different mode of life may play a significant role in expanding the set of strategies exploitable in the terrestrial realm. Additionally, species transitioning between terrestrial and aquatic realms, such as seals, exhibit intermediate life history strategies. Our results provide compelling evidence of the link between environmental realms and the life history diversity of mammals, highlighting the importance of differences in mode of life to expand life history diversity.

Killer whales of the Strait of Gibraltar, an endangered subpopulation showing a disruptive behavior - Ruth Esteban; Alfredo López; Álvaro Garcia de los Rios; Marisa Ferreira; Francisco Martinho; Paula Méndez‐Fernandeza; Ezequiel Andréu; José C. García‐Gómez; Liliana Olaya‐Ponzone; Rocío Espada‐Ruiz; Francisco J. Gil‐Vera; Cristina Martín Bernal; et al. (Marine Mammal Science, 2022)

Health-related quality of life in well-differentiated metastatic gastroenteropancreatic neuroendocrine tumors - P. Jiménez-Fonseca; A. Carmona-Bayonas; E. Martín-Pérez; G. Crespo; R. Serrano; M. Llanos; C. Villabona; R. García-Carbonero; J. Aller; J. Capdevila; E. Grande (Cancer and Metastasis Reviews, 2015)

Recruitment patterns in the Mediterranean deep-water alga Cystoseira zosteroides - P. Capdevila; C. Linares; E. Aspillaga; L. Navarro; D. K. Kersting; B. Hereu (Marine Biology, 2015)

Innovations therapy: mammalian target of rapamycin (mTOR) inhibitors for the treatment of neuroendocrine tumors - Jaume Capdevila; Ramón Salazar; Irene Halperín; Albert Abad; James C. Yao (Cancer and Metastasis Reviews, 2011)

A Glycine N-methyltransferase Knockout Mouse Model for Humans with Deficiency of this Enzyme - Zigmund Luka; Antonieta Capdevila; José M. Mato; C. Wagner (Transgenic Research, 2006)

Analysis of genes involved in 6-deoxyhexose biosynthesis and transfer in Saccharopolyspora erythraea - M. Doumith; P. Weingarten; U. F. Wehmeier; K. Salah-Bey; B. Benhamou; C. Capdevila; J.-M. Michel; W. Piepersberg; M.-C. Raynal (Molecular Genetics and Genomics, 2000)

Archaeobotanical remains of hulled and naked cereals in the Iberian Peninsula - R. Bux i Capdevila; N. Alonso; D. Canal; C. Echave; I. Gonzlez (Vegetation History and Archaeobotany, 1997)